2021
DOI: 10.1128/jvi.00432-21
|View full text |Cite
|
Sign up to set email alerts
|

A New Type of Satellite Associated with Cassava Mosaic Begomoviruses

Abstract: Cassava mosaic disease (CMD), which is caused by single-stranded DNA begomoviruses, severely limits cassava production across Africa. A previous study showed that CMD symptom severity and viral DNA accumulation increase in cassava in the presence of a DNA sequence designated as SEGS-2 ( s equence e nhancing g eminivirus s ymptoms). We report here that when SEGS-2 is co-inoculated with African cassava mos… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
16
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(17 citation statements)
references
References 63 publications
1
16
0
Order By: Relevance
“…Whiteflies are separated into genetic biotypes based on mtCOI sequences (Mugerwa et al, 2012 , 2018 ; Manani et al, 2017 ). The SSA1-SG1 and SSA1-SG2 biotypes have been associated with severe CMD (Ndunguru et al, 2016 ; Aimone et al, 2021a ). A recent study found SSA1-SG1, SSA1-SG2, and SSA2 biotypes in western Kenya and SSA2 and SSA1-SG3 biotypes in coastal Kenya (Munguti et al, 2021 ).…”
Section: Discussionmentioning
confidence: 99%
“…Whiteflies are separated into genetic biotypes based on mtCOI sequences (Mugerwa et al, 2012 , 2018 ; Manani et al, 2017 ). The SSA1-SG1 and SSA1-SG2 biotypes have been associated with severe CMD (Ndunguru et al, 2016 ; Aimone et al, 2021a ). A recent study found SSA1-SG1, SSA1-SG2, and SSA2 biotypes in western Kenya and SSA2 and SSA1-SG3 biotypes in coastal Kenya (Munguti et al, 2021 ).…”
Section: Discussionmentioning
confidence: 99%
“…The geminivirus beet curly top virus also causes strong symptoms on Sei-0, likely because it accumulates to high levels (Park et al 2004; Lee et al 1994), but differences in DNA-A and DNA-B levels in Col-0 vs. Sei-0 were variable in our experiment (Supplemental Table S1). Sei-0 can be infected with African cassava mosaic virus, whereas Col-0 cannot (Aimone et al 2021a). The genetic basis for the hypersusceptibility of Sei-0 is currently unknown but could be genetically mapped.…”
Section: Discussionmentioning
confidence: 99%
“…Single-stranded DNA (ssDNA) viruses belong to the largest known family of plant DNA viruses [ 16 ]. Other types of DNA-based viruses, such as African cassava mosaic virus (ACMV) and Cotton leaf crumple virus (CLCrV), have been efficiently converted into VIGS vectors and successfully applied to cassava and cotton plants [ 17 , 18 ]. RNA viruses are the earliest and most widely used viral vector to establish the VIGS system, due to their small molecular weight and high infection efficiency.…”
Section: Vigs Vectors For Gene Functional Analysis In Cottonmentioning
confidence: 99%